The Effects of Medical Debt Relief: Evidence from Two Randomized Experiments - Raymond Kluender; Neale Mahoney; Francis Wong; Wesley Yin (The Quarterly Journal of Economics, 2025)
Abstract Two in five Americans have medical debt, nearly half of whom owe at least $2,500. Concerned by this burden, governments and private donors have undertaken large, high-profile efforts to relieve medical debt. We partnered with RIP Medical Debt (now Undue Medical Debt) to conduct two randomized experiments that relieved medical debt with a face value of $169 million for 83,401 people between 2018 and 2020. Our experiments focused on downstream medical debt that had been sold to debt collectors, and one of our experiments straddled an industry-wide pullback in the reporting of medical debt to the credit bureaus, allowing us to estimate the effects of debt relief with and without counterfactual reporting. We track outcomes using credit reports, collections account data, and a multimodal survey. There are three sets of results. First, we find a modest improvement in credit access when there is counterfactual credit reporting, but no impact on credit report outcomes when there is not. Second, we estimate that debt relief causes a moderate but statistically significant reduction in payments of existing medical bills. Third, we find no effects on survey measures of mental and physical health, healthcare utilization, and financial wellness. Taken together, our results indicate that the strong correlations documented in prior research do not translate into causal effects for downstream medical debt relief.